Effective foreign language training through educational technology with the use of dictionaries - Kyrykylytsia, Valentyna V.; Кирикилиця, Валентина Василівна (National Technical University of Ukraine "Igor Sikorsky Kiev Polytechnic Institute", Faculty of Linguistics, 2017)
The article introduces the educational technology with the use of dictionaries into the process of foreign language training of the students of non-linguistic specialties. The author defines this technology as an algorithm of teachers and students’ common actions aimed at formation the abilities and skills of working with dictionaries of different types, learning the information obtained from dictionaries and its usage in the further practical activity. The paper demonstrates the convincing superiority of the newly developed technology which, under methodically correct conditions of its application, can significantly improve the qualitative indicators of the educational process. This hypothesis was confirmed by the results of the research conducted in 2016/2017 academic year at non-linguistic faculties of Lesya Ukrainka Eastern European National University. 183 first and second year students, among them 92 students of the experimental group (EG) and 91 students of the control (CG) one, were involved in the research. The study of the discipline “Profession-Oriented Foreign Language Study” in EG was carried out in the form of experimental teaching by means of the suggested technology while in CG traditional methods of teaching were used. The comparison of the students’ knowledge results obtained before and after the experiment allows us to state that there is a substantial increase in foreign language proficiency of EG students compared with the students in CG. This paper mainly presents the idea that application of the suggested technology ensures continuity and consistency of a foreign language acquisition, and a gradual transition from training to future professional activities.
Keywords: foreign language training; the students of non-linguistic specialties; dictionary; abilities and skills; dictionary activity; educational technology with the use of dictionaries